Spatial and Temporal Variations in the Water Quality of the Maroon River in the Maroon Dam Basin - N. Zalaki; M. Salari; Gh. Sayyad; K. Hemmadi (مهندسی منابع آب, 2013)
Water quality is a matter of utmost importance as it determines its suitability for particular purposes. As rivers are the lifelines everywhere, especially in an environments having information regarding the quality of their water is extremely useful for the water users. As a river’s water quality varies with the seasons of the year and the geological formations through which it flows, establishing a trend as to where and when to expect certain changes in the quality of a river’s flow gains importance. It is fortune that the newly developed technologies facilitate achieving these objectives. Therefore, we used the GIS and the Rockware software and the data collected during the 2000-2004 period at 2 hydrometry stations on the Maroon River to better classify the water quality spatially and temporally. The Chemical analyses consisted of pH, EC, TDS, CL, SO4, Ca, Mg, and NaCo3. It was revealed that the water quality deteriorated from the rainy season towards the dry season. Furthermore, as the river advanced from the mountainous area towards the low-laying plains the quality diminished, too. Most of the water samples were low in Cl and So4 conceal rations according to the Schoeller’s diagram; therefore suitable for drinking. According to the Wilcox’s classification, the water at the Aydnak station was in the C3S1 class and at the Dehnavi station was in the C2S1 class, both suitable for irrigation purpose.